"Shut up and dribble": fans' perceptions of professional athletes' role in standing up against racial injustices. Issue 1 (1st January 2023) - Rey, Rikishi T.; Capra, Johnny
ABSTRACT: The study of sport fandom has increased throughout the years as sport is often viewed as a microcosm of the larger society. To date, sports and social justice movements are extensively intertwined, and now, simply rooting for a team may indicate one's personal stance on societal issues. Therefore, this study sought to understand how one's fandom, knowledge of systematic racism, systemic racism, and BLM misconceptions relates to perceptions of athlete activism. Results indicate that fans ( N = 153) who watch for entertainment are the most supportive of athlete's using their platforms, whereas those who believe that athletes should "shut up and dribble" possess a lesser understanding of systematic and systemic racism and higher levels of BLM misunderstanding.